Giant Verruca Vulgaris of the Auricle Mimicking Verrucous Carcinoma: A Diagnostic and Surgical Case Study - Mega Ayu Saptaningrum; Pradhana Fajar Wicaksana (Sriwijaya Journal of Surgery, 2026)
Introduction: Verruca vulgaris, universally recognized as the common wart, represents a benign epithelial proliferation induced by the human papillomavirus (HPV). While these lesions are ubiquitous in the general population, typically manifesting as small hyperkeratotic papules on the acral regions, the occurrence of giant variants exceeding 2 centimeters in diameter on the auricle is an exceptionally rare clinical entity. This unusual presentation creates a significant diagnostic dilemma for the head and neck surgeon, as giant auricular warts frequently mimic the clinical presentation of malignant neoplasms, specifically verrucous carcinoma and squamous cell carcinoma. Case presentation: We document the case of a 36-year-old Indonesian male who presented with a massive, painless, exophytic mass on the posterior aspect of the right auricle. The lesion had persisted for ten years, exhibiting a slow, linear growth trajectory without spontaneous regression. Physical examination revealed a solitary, sessile, papillomatous lesion measuring 3.3 cm × 1.5 cm × 1.0 cm. Despite its alarming size, the mass remained mobile over the underlying perichondrium. Given the giant dimensions and the inability to rule out malignancy via visual inspection, the patient underwent total surgical excision with primary closure under general anesthesia. Histopathological analysis confirmed the diagnosis of verruca vulgaris, characterized by marked hyperkeratosis, papillomatosis, and pathognomonic koilocytosis, with an intact basement membrane ruling out invasive carcinoma. Conclusion: Giant verruca vulgaris of the auricle is a rare pathology that requires a rigorous diagnostic approach. We conclude that auricular verrucous lesions exceeding 2 centimeters should be clinically managed as tumors of uncertain potential. Surgical excision remains the diagnostic and therapeutic gold standard, offering immediate aesthetic restoration and the essential histopathological confirmation required to differentiate benign giant warts from the deceptive pushing border of verrucous carcinoma.